HOW TO BE A GOOD LANGUAGE TEACHER - Saadillah, Saadillah (English Department of Faculty of Tarbiyah and Teachers Training, 2012)
AbstractThere are two Â crucial questions about the study of language Â teacher. The first Â question is âHow is a good Â Â teacher?â The second question is âHow is a good language teacher? Â To answer those questions, it should be understood that teacher is a usual creation of God. Like an English proverb saysâthere is no one Â perfect Â so, the teacher maybe will do the mistakes. The teacher maybe has some weakness . Â This writing tries describing some facts about teachers as general, and introducing the Â reader about how is going to be a good language teacher. Â